The Philippine wildlife [slides]. (Makati Felta Book Sales)
Discover the colorful variety of what is left of our teeming wildlife. Differentiate between migratory and endemic species. Understand the different peculiarities of these animals which are their means for survival.
Keywords: Zoology -- Philippines; Natural Sciences